EMPOWERMENT OF MOTHERS OF CHILDREN UNDER TWO THROUGH EDUCATION AND LOCAL COASTAL FOOD-BASED COMPLEMENTARY FEEDING TRAINING FOR STUNTING PREVENTION - Herta Masthalina; Tetty Herta Dolok Saribu; Mincu Manalu (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Stunting remains a significant public health challenge in Indonesia. Bagan Serdang Village, a coastal area in Deli Serdang Regency, recorded stunting and underweight rates among children under two of 25.9% and 29.6%, respectively, exceeding national averages. Despite abundant local marine resources, only 25.9% of mothers had good knowledge, and 37% had good skills in processing local food-based complementary feeding. This program aimed to improve mothers' knowledge and skills in preparing local coastal food-based complementary feeding for stunting prevention. A participatory community empowerment approach was applied involving 27 mothers of children under two, 5 posyandu cadres, and 5 PKK members in Bagan Serdang Village from February to May 2026. Activities included nutrition counselling through interactive lectures and booklet-based education, and complementary feeding preparation practice using local coastal food ingredients (lemuru fish, yellow stripe scad, and small shrimp). Knowledge and skills were assessed through pre-test and post-test questionnaires and direct observation checklists, analyzed descriptively. Knowledge in the good category improved significantly from 25.9% to 100%, while skills improved from 37.0% to 100%. The greatest improvement occurred in understanding the nutritional value of local coastal food and hygienic processing techniques. Five local food-based complementary feeding recipes were developed along with a nutrition education booklet and recipe book distributed to all participants. The combination of interactive counselling, cooking demonstrations, and direct practice proved highly effective, consistent with findings from similar studies. The empowerment program significantly improved mothers' knowledge and skills in local coastal food-based complementary feeding for stunting prevention. The participatory approach is replicable in other coastal areas with similar marine resource characteristics.